The Effect of Executive Compensation on Credit Default Swap Spread - Meizaroh Meizaroh; Masripah Masripah (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2019)
Investors have been trying to formulate the optimum composition of executives’ compensation which will incentivize the executives to perform better and act in the shareholders’ best interests. This study aims to find empirical evidence about the impact of executive compensation on the default risk with the Credit Default Swap (CDS) spread as the proxy, using panel data to test the research model, which combines the analysis of cross-section and time series data. The study is conducted based on 1,416 observations of 177 U.S. companies from 2008-2015. The data are mainly collected from Datastream, Compustat, CRSP, and the US SEC’s EDGAR database. The current study provides a contribution by suggesting that executives’ compensation will trigger risk-taking behavior. The results of this study reveal, firstly, both equity-based compensation and debt-like compensation induce risk-taking behavior by the executives. Secondly, the correlation between both the form of the compensation and the CDS spread is weakened in a high information asymmetry environment. Lastly, this study finds that a CFO’s compensation has more influence on the CDS spread, compared to the other board executives, but this condition only occurs when the compensation is awarded in the form of debt-like compensation. To improve the generalization of the results, a further study may consider expanding the sample into several countries.